Effectiveness of information and communications technology interventions for stroke survivors and their support people: a systematic review. - Freund, Megan; Carey, Mariko; Dilworth, Sophie; Waller, Amy; Mansfield, Elise; Rose, Anna; Thienel, Renate; Hyde, Lisa (Disability & Rehabilitation, 2022)
To examine the effectiveness of self-directed, off-the-shelf information and communications technology (ICT)-based interventions in improving the quality of life, physical and psychosocial outcomes of community-dwelling stroke survivors and their support persons (SP). Medline, EMBASE, CINAHL and Cochrane databases were searched (2006–19th June 2020) for randomized controlled trials, controlled trials, controlled before and after studies, or interrupted time series studies that met the eligibility criteria. The quality of included studies was assessed. Interventions effectiveness was narratively synthesized, as was participant adherence and acceptability. Seventeen studies were eligible. Three studies were rated as low risk of bias across all methodological review criteria. Nine studies reported on interventions delivered using self-directed computer programs, two studies utilized internet or web-based support programs and six studies used mobile phone interventions. Few studies reported on intervention acceptability or adherence. Those that did generally reported good acceptability, although adherence was variable. Fifteen studies reported significant positive effects for at least one outcome examined including stroke-specific outcomes, physical outcomes, behavioural outcomes and health service use. No studies found an effect for psychosocial wellbeing. ICT-based interventions are likely to provide benefit to stroke survivors and their SPs. However, there is a need for further robustly designed intervention studies that include larger sample sizes, longer follow-up, and outcomes for SPs. ICT-based interventions with minimal clinician supervision are likely to provide some benefits to stroke survivors and their SPs. There is insufficient evidence to allow recommendations to rehabilitation professionals regarding the type, length and intensity of ICT-based interventions for specific targeted outcomes. Rehabilitation professionals should use professional judgement prior to recommending ICT-based interventions to stroke survivors and their SPs.